Ultrasonic softening-hardening mechanism and constitutive model for ultrasonic riveting of 2A10 aluminum alloy - Heng Zhang; Weijun Liu; Zewei Yuan (Journal of Materials Research and Technology)
Ultrasonic riveting (UR) effectively improves riveting quality, thereby enhancing the safety and reliability of aircraft structures. This study proposes a method for constructing an UR constitutive relationship model and combines systematic experimental analysis to scientifically investigate the mechanism by which UR improves riveting quality. This study explores the impacts of ultrasonic softening-hardening effects on the riveting stress-strain under different strain rates and amplitudes, as well as the microstructural evolution of the rivets at various amplitudes. The results of this study indicate that ultrasonic vibration has a remarkable effect on decreasing the riveting stress. When the amplitude is 8.83 μm and the strain rate is 1.43 × 10 s−1, the yield strength of the rivets decreases by 56.04 %. In this study, the rivets exhibit a residual softening phenomenon, and the residual hardening effect intensifies as the amplitude increases. Electron backscatter diffraction (EBSD) analysis showed that ultrasonic vibration could promote the formation of low-angle grain boundaries (LAGB) and achieve grain refinement. When the amplitude was increased from 5.64 μm to 8.83 μm, the LAGB in the range of 2°–15° increased by 35.26 % and the number of grains increased by 96.07 %. This study also constructs a UR constitutive model that takes into account the changes in amplitude. Compared to experimental data, the average accuracy of this model is 99.638 %. The results of this study contribute to the promotion of the application of ultrasonic vibration in the riveting process.